Colonization and infection in tracheostomized patients at tertiary care hospital in Eastern Nepal (Health Renaissance, 2015)
Introduction: Tracheostomy is a life saving emergency procedure and provides many benefits for long term ventilator dependent patients. However, colonization and infection of airways after tracheostomy is one of the serious complications increasing patient morbidity and mortality. Objective: To find out the colonizing agent in the trachea of tracheostomized patients and the type and frequency of post tracheostomy infection. Methods: Study was conducted in 30 consecutive, adult patients requiring either elective or emergency tracheostomy at BPKIHS, Nepal. First and second tracheal swab was obtained immediately after tracheostomy and on the seventh day. Micro-organisms isolated from the culture of tracheal swab were noted. Patients were observed for infectious complications after tracheostomy. Results: Eighteen (60%) tracheostomies were performed electively and 12(40%) as an emergency. Sixty-eight isolates were grown from the culture of tracheal swabs. Out of 60 tracheal swabs, nine showed sterile culture. Single micro-organism was isolated from 35(58.33%) tracheal swabs and polybacterial isolation was seen in 16(26.66%) swabs. Pseudomonas aeroginosa was the commonest micro-organism isolated. After Pseudomonas, Staphylococcus aureus in the first culture and Acinetobacter anitratus in the second culture was the commonest organisms isolated. Five (16.6%) patients developed stomal infection and three (10.0%) developed pneumonia as a complication of tracheostomy. Conclusion: Trachea of the tracheostomized patients is heavily colonized by Pseudomonas aeruginosa, Acinetobacter anitratus and Staphyloccus aureus . Stomal infection and pneumonia are the infectious complication occurring within seven days of tracheostomy.Health Renaissance 2014;12(2): pp. 68-73